Exploring the relationship and shared mechanisms of major depressive disorder and diabetic kidney disease: a comprehensive clinical and genetic analysis - Liu, Huan-xi; Wang, Ting-ting; Cheng, You-di; Qu, Chun-hui; Feng, Shun-kang; Wang, Xiang-wen; Wu, Xiao-hui; Sun, Wen-xi; Sun, Ping (Frontiers in Psychiatry, 2025)
IntroductionMajor depressive disorder (MDD) is a common comorbidity in diabetes mellitus (DM), while diabetic kidney disease (DKD) represents a severe complication of DM. However, the clinical and genetic associations between MDD and DKD remain unclear. This study aimed to investigate their shared biomarkers, molecular pathways, and immune features.MethodsWe analyzed data from the National Health and Nutrition Examination Survey (NHANES, 2005–2018) to assess the association between MDD and DKD. Genetic correlation was evaluated using linkage disequilibrium score regression (LDSC), and causality was tested with Mendelian randomization (MR). Gene expression datasets were integrated to identify crosstalk genes, followed by protein–protein interaction (PPI) analysis to detect hub genes. Diagnostic performance was validated using least absolute shrinkage and selection operator (LASSO) regression and receiver operating characteristic (ROC) curves. Immune infiltration was assessed, and potential therapeutic compounds were predicted through connectivity map (cMAP) analysis and molecular docking.ResultsClinical analysis revealed a significant association between MDD and DKD (OR = 1.45, 95% CI: 1.28–1.64). LDSC indicated a significant genetic correlation (r = 0.2153, P = 0.008), although MR analysis did not support a causal relationship. A total of 83 crosstalk genes were identified, primarily enriched in inflammation and immune regulation pathways. PPI analysis highlighted eight hub genes, with CD163 and KLRB1 emerging as promising shared diagnostic biomarkers. Validation using LASSO and ROC confirmed their diagnostic potential. Immune infiltration analysis revealed shared immune cell alterations. Furthermore, cMAP analysis and molecular docking suggested rucaparib and levocetirizine as candidate therapeutic agents.DiscussionOur findings demonstrate a genetic and immunological link between MDD and DKD. CD163 and KLRB1 may serve as potential biomarkers and therapeutic targets, offering new insights into the shared mechanisms and treatment strategies for comorbid MDD and DKD.